(untitled) - Lougheed, Lin (White Plains, N.Y., 2012)
The longman Preparation Series for the TOEIC Test: Listening and Reading will teach you language strategies and test strategies that will help you reach these goals and score well on the TOEIC test.
Keywords: English language,Tiếng Anh; Business English,Examinations,Tiếng Anh thương mại,Kỳ thi